Power over prosecutors corrupts politicians: cross country evidence using a new indicator - Anne van Aaken; Lars P. Feld; Stefan Voigt (Center for Economic Studies and ifo Institute (CESifo), 2008)
It is hypothesized that prosecution agencies that are dependent on the executive have less incentives to prosecute crimes committed by government members which, in turn, increases their incentives to commit such crimes. Here, this hypothesis is put to an empirical test focusing on a particular kind of crime, namely corruption. In order to test it, it was necessary to create an indicator measuring de jure as well as de facto independence of the prosecution agencies. The regressions show that de facto independence of prosecution agencies robustly reduces corruption of officials.
Keywords: H11; K40; K42; 330; corruption; prosecution agencies; judicial independence and positive constitutional economics; Justiz; Gewaltenteilung; Korruption; Kriminalpolitik; Welt